The Effect of ESG Disclosure, Investment Decision, Funding Decision, and Dividend Policy on Firm Value (Study on SRI-KEHATI Index Companies Period 2019-2022) - Husnia, Alifatul; Isbanah, Yuyun (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
New companies that continue to grow every time require all companies, both existing and new companies to survive and compete to be the most superior through increasing firm value. This research aims to analyze the effect of ESG disclosure, investment decisions, funding decisions, and dividend policy on firm value. The population used in this research is companies that has been listed on SRI-KEHATI index on the Indonesia Stock Exchange in 2019-2022. This research used purposive sampling method, total sample for this research is 17 companies with 68 observation data from annual report and companies sustainability report for 4 years. The analytical method used in this research is multiple linier regressions analysis and hypothesis testing with using to help of SPSS 25 version. The result of this research showed that simultaneously ESG disclosure, investment decisions, funding decisions, and dividend policy affect firm value. ESG disclosure has a significant negative effect on firm value. Investment decisions has no effect on firm value. Funding decisions has a significant negative effect on firm value. Dividend policy has no effect on firm value. The implementation of ESG over a long period of time is able to provide great benefits for the company in the future, to increase company value and reduce the risks that may be experienced by the company due to poor environmental, social and governance management. Based on the result, for further research it would be better to use more period, so the development of ESG disclosure by the companies can be seen over a longer period of time.